(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This paper aims to discuss the pertinent characteristics for the design of a participatory model in the communicational, didactic and cultural spheres. For this, it makes use of bibliographic research, guided by a phenomenological look, resonant with the essayistic form of expression. It takes different perspectives, of which stand out Martin Buber, Paulo Freire, Juan Bustos, Vicente Romano, Victor Ventosa, Kristoffer Haggren and Vilém Flusser - the latter, responsible for the theoretical lens through which we look at design processes. As a result, it indicates the need for a dialogical and horizontal communication, guided by a model that educates for participation, celebrates the engagement and the discussion of the agreements and the necessary stimuli for the teaching-learning contexts.